APLIKASI TEKNOLOGI 3D PRINTER DALAM RANGKA PENGEMBANGAN PEMBUATAN KOMPONEN MINIATUR DI KARANG TARUNA DUSUN BENDUNGAN - Braam Delfian Prihadianto; Suryo Darmo (Institut Teknologi Dirgantara Adisutjipto, 2021)
Replica is an imitation of an object in a size that is greatly reduced by the level of precision and detail that resembles the original object. One of the replica commonly made is a replica of transportation, especially buses, and one of the producers is Karang Taruna Dusun Bendungan, which is located in Karangmojo Subdistrict, Gunung Kidul District. Making replica so far has been done manually by relying on the cutter as a forming tool. In making manuals there are several obstacles faced, namely difficulties when making molds which include cowl molds, seat molds, AC cover molds and other parts. In addition, making miniature manually has disadvantages such as not being precise in shape and size with the original object and if there is a small change in a particular part, then it must be made from scratch again. Based on these constraints the team provided a solution by making a 3D printer machine that could be used to support bus replica production. Making a 3D printer machine with dimensions of 48 x 46 x 44 cm got a positive response. In addition, the conducted training were enthusistically participated by the members. Utilization of 3D printer machines greatly helps the production process and increases the efficiency of time by 76% at the stage of making master prints.